Analisis SNR pada Variasi Reduction Factor Sensitivity Encoding MRI Brain Sekuens DWI Axial - Hernastiti Sedya Utami; Fani Susanto; Arga Pratama Rahardian; Muhammad Erfansyah (Poltekkes Kemenkes Semarang, 2021)
Backgroud: Brain MRI examination generally has a long scanning time because many protocols that must be used, one of them is DWI sequences, which are sequences that can provide pathological information on the brain. One way to reduce scan time is to use parallel imaging sensitivity encoding (SENSE) techniques. SENSE utilizing the spatial information RF coil phased array to reduce the acquisition time by reducing the number of sampling lines K space therefore produce quality and good spatial resolution, but its has the limitations, namely the reduction of SNR. The purpose of this research was to analyze in SNR on the variations of SENSE value in MRI brain DWI axial slices.Methods: This research is a quantitative study with an experimental approach in 15 patients MRI Brain. Data was taken by calculating the SNR value for the region of interest (ROI) in cortex cerebri, basal ganglia, thalamus, pons and cerebellum, and then ROI in noise background. Data was analyzed through Repeated Measures Anova test by comparing the differences in SNR values obtained in MRI brain DWI axial between the use of various SENSE values, that are 2.0; 3.0 and 4.0.Results: MRI image of DWI axial brain sequence with variation of reduction factor 2.0; 3.0 and 4.0 cause different SNR values. The highest SNR is found in the variation of 2.0 and the lowest value is 4.0 but the scan time is fastest at the 4.0 variation This is because there is a reduction in the phase encoding line in the K-space on each image using SENSE and the higher the reduction factor, the higher the reduction factor. SNR will decrease.Conclusion: The higher the value of SENSE variations will decrease the SNR value but the scan time is faster.